Silverlight 2 Recipes A Problem-Solution Approach - Ghosh, Jit; Cameron, Rob (Apress : Imprint: Apress, 2009)
Microsoft .NET architect evangelist Jit Ghosh presents a practical companion guide to developing rich, interactive web applications with Silverlight 2. Common problems, issues, and every-day scenarios are tackled with a detailed discussion of the solution and ready-made code recipes that will save you hours of coding time. The recipes included in Silverlight 2 Recipes: A Problem-Solution Approach have been carefully selected and tested with the professional developer in mind. You'll find clearly and succinctly stated problems, well-architected solutions, and ample discussion of the code and context so you can see immediately how the solution will support your project. Enjoy practical coverage of Silverlight development in many projects and contexts, including Designing complete, rich, interactive user experiences Manipulating content and the runtime environment through the Silverlight Plugin Runtime API Consuming, transforming, and displaying content in your Silverlight web application through XML, LINQ-based data access, and isolated storage Building custom controls for your Silverlight project Integrating rich media, including audio and video, to create a very dynamic user interface and experience Using new Silverlight 2 features, including .NET Framework integration, the use of dynamic languages like Python and Ruby in Silverlight development, and digital rights management support Find instant solutions, comprehensive Silverlight 2 coverage, and time-saving expert advice, all in Silverlight 2 Recipes: A Problem-Solution Approach.